ENHANCING INNOVATIVE PEDAGOGY IN TEACHING ENGLISH AS AN INTERNATIONAL LANGUAGE FOR INDONESIAN LEARNERS - Moh. Yamin; Oikurema Purwati (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
English at present is not viewed as a foreign language concerning global needs that should be learned and understood by students with isolation. Therefore, English undergoes shifting from foreign into international language or English as International Language (EIL). This paper describes the importance of EIL teaching to Indonesian students through innovative pedagogy as an effort to speed their English competence in written and spoken. At present theories and research studies dealing with EIL and innovative pedagogies are presented. All confirm that it is time to teach EIL to make the students having their identity although they use English. In EIL, students respect the local identity while learning English. Innovative pedagogy is the instruction strategy to make the students interactive and interested in English. Hence, the teachers’ role in teaching English through innovative pedagogy is required. Teachers should use the students’ environment as teaching material with global knowledge.